1982
DOI: 10.1366/0003702824639286
|View full text |Cite
|
Sign up to set email alerts
|

Electron Number Density Measurements in Ar and Ar-N2 Inductively Coupled Plasmas

Abstract: The emission spectrum of the series limit of Al was used to estimate the electron number densities ( n e) in inductively coupled Ar or Ar-N2 plasmas (ICP). The spectra of the series limit were recorded either with a silicon-intensified target vidicon detector or by a computer-controlled, scanning spectrometer. Background stripping was performed on the spectra recorded by both instruments to enhance signal recovery. Under comparable experimental conditions, the n e values in the Ar-supported ICP were higher tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…The improved LODs were observed for elements such as As, Bi, Cd, P, S and Zn whose excitation energies were relatively higher viewing Ar-N2 ICPOES reported previously. [4][5][6][7][8][9][10][11][12][13][14] From these results, the Ar-N2 ICP could be useful as an optional excitation and ionization source in axially viewing ICPOES, especially for those elements with relatively higher excitation and ionization energies.…”
Section: Limits Of Detectionmentioning
confidence: 89%
See 1 more Smart Citation
“…The improved LODs were observed for elements such as As, Bi, Cd, P, S and Zn whose excitation energies were relatively higher viewing Ar-N2 ICPOES reported previously. [4][5][6][7][8][9][10][11][12][13][14] From these results, the Ar-N2 ICP could be useful as an optional excitation and ionization source in axially viewing ICPOES, especially for those elements with relatively higher excitation and ionization energies.…”
Section: Limits Of Detectionmentioning
confidence: 89%
“…2,3 In order to improve the analytical sensitivity as well as the analytical performance for either ICPOES or ICPMS, many examinations on the alternative plasma sources have been carried out instead of the Ar ICP as standard ICP. In the 1980's, mixed-gas ICPs such as Ar-N2 ICP, [4][5][6][7][8][9][10][11][12][13][14] Ar-O2 ICP, [10][11][12]14,15 Ar-He ICP, 10,11,13,15 Ar-Air ICP 10,11 and Ar-H2 ICP, 13 molecular-gas ICPs such as N2 ICP [16][17][18] and O2 ICP, [18][19][20][21][22] and He ICP, [23][24][25][26][27][28] were examined to achieve further improvement in the analytical sensitivity of elements instead of the standard (Ar) ICPOES. Since radial viewing ICPOES was mainly used in those days, most of the mixed-gas ICPs was examined in radial viewing OES.…”
Section: Introductionmentioning
confidence: 99%
“…The instrumentation used for the AES work has been described conditions for each instrument. The detection limits (3s) were in a previous paper51 and the instruments for N 2 -MIP-MS established as the detection capability for both plasma systems and Ar-ICP-MS were a P-6000 (Hitachi, Ibaraki, Japan) and using a total of 55 wavelengths (atom and ion lines) for 21 an HP-4500 (Yokogawa Analytical Systems, Tokyo, Japan), elements for AES and a total of 38 m/z values for 22 elements respectively. The plasma operating conditions and the measurefor MS.…”
mentioning
confidence: 99%
“…The LTE approach is advantageous in the sense that the plasma can be characterized with either or both of the two measurable parameters, i.e., temperature and electron density, thus providing a basis for theory-experiment comparison. Unfortunately, many diagnostical studies have indicated that LTE does not exist throughout the ICP (2, 7, [9][10][11]16,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43], rendering it inappropriate to mechanistic elucidation of analyte excitation. Furthermore, it treats the portion of plasma under investigation as a closed system, whereas the real plasma is everywhere dynamic and open.…”
Section: Literature Citedmentioning
confidence: 99%